2016
DOI: 10.14414/jebav.v19i1.537
|View full text |Cite
|
Sign up to set email alerts
|

The effect of employment, economic growth, and investment on HDI: In provinces in Indonesia

Abstract: This study aims to analyze the effect of Number of Working People (Employment), Economic Growth Rate (EGR), and Investment on Human Development Index (HDI) in Indonesia, partially and simultaneously. This study used investments consisting of Domestic Investment (DI) and Foreign Direct Investment (FDI). It used the method of analysis of panel data regression analysis with the data from thirty-three provinces in Indonesia from 2006 to 2013. The results indicate that the employment variables have positive and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
11
1
5
Order By: Relevance
“…The results of this study are in line with the findings study by Elistia & Syahzuni (2018); Grubaugh (2015); Harahap et al (2020); Bhakti (2014) and Sangaji (2016) found that economic growth had a significant effect on HDI. In addition, these findings contradict the findings study by Feriyanto (2016); Meydiasari & Soejoto (2017);and Barus et al (2021) found that economic growth had no effect on HDI.…”
Section: Source: Authors Computationcontrasting
confidence: 63%
“…The results of this study are in line with the findings study by Elistia & Syahzuni (2018); Grubaugh (2015); Harahap et al (2020); Bhakti (2014) and Sangaji (2016) found that economic growth had a significant effect on HDI. In addition, these findings contradict the findings study by Feriyanto (2016); Meydiasari & Soejoto (2017);and Barus et al (2021) found that economic growth had no effect on HDI.…”
Section: Source: Authors Computationcontrasting
confidence: 63%
“…Bhowmik (2019)found that a one per cent increase in the unemployment rate per year caused a significant decrease of 0.027% in the annual human development index in the ASEAN economy. Also, Feriyanto (2016) show that the employment variable has a positive and significant impact on the human development index in Indonesia. Then an increase in the minimum wage will result in reduced birth rates [Bullinger (2017); Kreyenfeld and Andersson (2013); Del Boca and Sauer (2009); Apps and Rees (2004)].…”
Section: C) Joint Determination Of Social Variablesmentioning
confidence: 92%
“…Feriyanto's research (2016) shows that the employment variable has a positive and significant effect on HDI in Indonesia, while economic growth has no impact on Indonesia's HDI. However, PMDN and PMA partially have a significant positive effect on HDI in Indonesia [15].…”
Section: Human Development Index and Islamic Human Development Indexmentioning
confidence: 89%